Enamel Based Composite Layers Deposited on Titanium Substrate with Antifungal Activity. (12th December 2016) - Iconaru, S. L.; Prodan, A. M.; Turculet, C. S.; Beuran, M.; Ghita, R. V.; Costescu, A.; Groza, A.; Chifiriuc, M. C.; Chapon, P.; Gaiaschi, S.; Hristu, R.; Stanciu, G. A.; et al.
Abstract : The goal of this paper was to investigate the antifungal activity of Enamel layers deposited on titanium substrate (Ti-Enamel) and Enamel layers deposited on titanium substrate previously coated with a vinyl polydimethylsiloxane layer (Ti-PDMS-Enamel). The physicochemical properties were also investigated. The Candida albicans biofilm development on the obtained layers was examined after 24 h, 48 h, and 72 h by confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM) after ethidium bromide staining. A significant inhibition of the fungal adherence and biofilm development was observed on Ti-Enamel layers. The antifungal results demonstrated that the use of new Ti-Enamel composite layers could represent a promising perspective for the prevention of fungal biofilms associated implant infections.